PRODUKSI MINUMAN FUNGSIONAL BERBASIS SUSU DAN LABU KUNING : STRATEGI PENGEMBANGAN KETAHANAN PANGAN - Sri Hartatie, Endang; Khotimah, Khusnul (Jurnal Gamma, 2012)
PRODUKSI MINUMAN FUNGSIONAL BERBASIS SUSU DAN LABU KUNING : STRATEGI PENGEMBANGAN KETAHANAN PANGANEndang Sri Hartatie1 & Khusnul Khotimah21&2Staf Pengajar Jurusan Teknologi Industri Peternakan, Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Malang e-mail: 1)endang@umm.ac.id, 2)thuthul17@yahoo.com ABSTRACTIce cream is a very popular snack all over the world. Ice cream though assumed to originate from China, this product is already a special dish in many countries.Ice cream is a kind of semi-solid foods made with flour freezing of ice cream or a mixture of milk, animal and vegetable fats, sugar, with or without other foods and food ingredients that are allowed.Ice cream component consists of protein, fat, sugar, colorings, flavor and need additional material to stabilize the emulsion pemantap in a solution of milk fat and improve the texture of ice cream.This study aims to develop a form of functional beverages or health food (Nutraceutical Food) based milk and pumpkin to make ice cream products, as a strategy for the development of food security.The conclusion of this study is an herbal ice cream low-fat, can be made with a mixture of pumpkin and yogurt as a substitute for skim milk and cream by 15% of the total mixture or pumpkin 100gram and 200 gram of liquid yogurt. In the organoleptic texture formula D 4.85, which means very close to 5 and preferably low fat and protein composition, and have climbed the highest score. In orgasnoleptik formula D is a complete ice cream, soft and not easy to melt. Melting time up to 2 hours for all formula.Keywords: ice cream herbal, health food / functional, yellow squash